2023
DOI: 10.1186/s13102-023-00619-1
|View full text |Cite
|
Sign up to set email alerts
|

Listening to music during a repeated sprint test improves performance and psychophysiological responses in healthy and physically active male adults

Abstract: Background It is well-documented that listening to music has the potential to improve physical performance during intense physical exercise. Less information is available on the timing of music application. This study aimed to investigate the effects of listening to preferred music during the warm up of a subsequent test or during the test on performance of repeated sprint sets (RSS) in adult males. Methods In a randomized cross-over design, 19 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Just listening to fast (140 beats/min) and loud (80 dB) music during warm-up has been shown by Ouergui et al [24] to enhance kicking performance during the 10 s and multiple 10 sec kicking test in taekwondo athletes. Other studies [22,24] also indicated that the use of preferred music with a fast tempo (>140 beats/min) presents an effective strategy to improve physical performance, probably due to the motivational self-regulation of the music [22,23]. Due to the earlier findings of the positive effects on performance by the use of music during the warm-up, this condition was not included in the present study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Just listening to fast (140 beats/min) and loud (80 dB) music during warm-up has been shown by Ouergui et al [24] to enhance kicking performance during the 10 s and multiple 10 sec kicking test in taekwondo athletes. Other studies [22,24] also indicated that the use of preferred music with a fast tempo (>140 beats/min) presents an effective strategy to improve physical performance, probably due to the motivational self-regulation of the music [22,23]. Due to the earlier findings of the positive effects on performance by the use of music during the warm-up, this condition was not included in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Besides video feedback, previous studies reported that listening to music during warm-up can also enhance physical performance [21][22][23][24]. In fact, the ergogenic effects of listening to music on physical performance, based on its motivational strategy, is attributed to the delayed perception of afferent signals related to neurological fatigue [25], improving muscular efficiency [26], neural activity [27], positive mood [22], attention [28], and selfefficacy [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this scale was developed to measure such responses. Previous studies recommended this scale to measure affective response after exercise [ 18 , 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a psychological aid during exercise, listening to music has been shown to improve mood/affect, enjoyment, motivation, and RPE [ 16 ]. Furthermore, inherent characteristics of music, such as musical tempo, have been shown to alter pacing strategy and improve exercise efficiency in aerobic [ 17 , 18 ] and anaerobic exercise [ 19 , 20 ]. However, conflicting reports exist with some studies reporting little to no effects of music on jump height during squat jumps [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each player responded to the question: "How did you perceive your exertion in your full-body during the test?". Previous studies have recommended this scale to measure RPE after exercise (Jebabli et al, 2022;Jebabli et al, 2023).…”
Section: Vameval Test and Time To Exhaustionmentioning
confidence: 99%